The Impact of Earnings Management and Distress on Tax Aggressiveness: The Role of Company Size - Lestari, Ayu Endah; Melzatia, Shinta; Melzatia, Haura Hazimah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Taxes are a critical source of national revenue and play a central role in maintaining economic stability, particularly in emerging economies such as Southeast Asia. The growing intensity of corporate tax planning practices has created challenges in ensuring effective tax collection. Specific Background: In Indonesia, corporations often perceive taxes as a financial burden, leading to strategic behaviors aimed at minimizing tax obligations. Such practices hinder the government's ability to achieve its fiscal targets. Knowledge Gap: Although prior studies have examined various determinants of tax aggressiveness, limited research has integrated earnings management, financial distress, and thin capitalisation into a single analytical framework, particularly considering the moderating role of firm size. Objective: This study investigates the influence of earnings management, financial distress, and thin capitalisation on corporate tax aggressiveness, while also exploring whether firm size moderates these relationships. Methods: The study employs panel data from 19 raw material companies in Indonesia over the 2018–2022 period (145 firm-year observations), using multiple regression analysis with EViews 12. Results: Earnings management and financial distress have a significant positive effect on tax aggressiveness, whereas thin capitalisation does not. Firm size moderates the effects of earnings management and financial distress, but not thin capitalisation. Novelty: This research offers an integrated model that combines multiple financial dimensions to explain tax aggressiveness behavior. Implications: The findings provide strategic insights for policymakers and tax authorities to improve regulatory frameworks and strengthen oversight, especially in capital-intensive industries.